Impact of the COVID-19 Pandemic on the Physical Activity Profile and Glycemic Control Among Qatari Adults With Type 1 Diabetes: Effect of Vaccination Status - Georges Jabbour; Souhail Hermassi; Nicola Bragazzi; Nicola Bragazzi (Frontiers Media S.A., 2022)
ObjectiveTo investigate the impact of COVID-19, as an influent barrier on physical activity (PA) patterns and glycemic control in Qatari adults with type 1 diabetes (T1D). As the COVID-19 vaccine may have a potential impact on an individual's lifestyle, we also considered this parameter.MethodsPhysical activity level, the exercise barriers (BAPAD1), anthropometric characteristics, the method of insulin administration, and the last glycated hemoglobin in % were completed by 102 Qatari adults with T1D. Moreover, all patients were asked whether they had "been vaccinated" or had a "fear of being infected by COVID-19".ResultsFor the unvaccinated group, weight, BMI and HbA1c (%) were significantly higher than those of vaccinated group (p < 0.01) and engaged in less moderate-to-vigorous PA (MVPA) (p < 0.01) per week and had less time in vigorous PA (VPA) (p < 0.01). A significant association between VPA levels and BMI (β = −0.36, p = 0.02) and HbA1C (%) (β = −0.22; p = 0.03) was reported, and "being vaccinated" was significantly associated with MVPA (β = 0.15; p = 0.021) and VPA (β = 0.28; p = 0.032). A higher "Fear of being infected by COVID-19" score was negatively correlated with reduced PA profiles (R2 = −0.71 for MVPA; R2 = −0.69 for VPA, p < 0.01, respectively).ConclusionPracticing VPA during the COVID-19 pandemic confer many health benefits for Qatari individual with T1D. As the "Fear of being affected by COVID-19" appeared as a potential barrier to PA practices this latter e.g. PA, could likely not be achieved without the participants being vaccinated.